(x-3)(x-2)=7x+30

Simple and best practice solution for (x-3)(x-2)=7x+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(x-2)=7x+30 equation:


Simplifying
(x + -3)(x + -2) = 7x + 30

Reorder the terms:
(-3 + x)(x + -2) = 7x + 30

Reorder the terms:
(-3 + x)(-2 + x) = 7x + 30

Multiply (-3 + x) * (-2 + x)
(-3(-2 + x) + x(-2 + x)) = 7x + 30
((-2 * -3 + x * -3) + x(-2 + x)) = 7x + 30
((6 + -3x) + x(-2 + x)) = 7x + 30
(6 + -3x + (-2 * x + x * x)) = 7x + 30
(6 + -3x + (-2x + x2)) = 7x + 30

Combine like terms: -3x + -2x = -5x
(6 + -5x + x2) = 7x + 30

Reorder the terms:
6 + -5x + x2 = 30 + 7x

Solving
6 + -5x + x2 = 30 + 7x

Solving for variable 'x'.

Reorder the terms:
6 + -30 + -5x + -7x + x2 = 30 + 7x + -30 + -7x

Combine like terms: 6 + -30 = -24
-24 + -5x + -7x + x2 = 30 + 7x + -30 + -7x

Combine like terms: -5x + -7x = -12x
-24 + -12x + x2 = 30 + 7x + -30 + -7x

Reorder the terms:
-24 + -12x + x2 = 30 + -30 + 7x + -7x

Combine like terms: 30 + -30 = 0
-24 + -12x + x2 = 0 + 7x + -7x
-24 + -12x + x2 = 7x + -7x

Combine like terms: 7x + -7x = 0
-24 + -12x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '24' to each side of the equation.
-24 + -12x + 24 + x2 = 0 + 24

Reorder the terms:
-24 + 24 + -12x + x2 = 0 + 24

Combine like terms: -24 + 24 = 0
0 + -12x + x2 = 0 + 24
-12x + x2 = 0 + 24

Combine like terms: 0 + 24 = 24
-12x + x2 = 24

The x term is -12x.  Take half its coefficient (-6).
Square it (36) and add it to both sides.

Add '36' to each side of the equation.
-12x + 36 + x2 = 24 + 36

Reorder the terms:
36 + -12x + x2 = 24 + 36

Combine like terms: 24 + 36 = 60
36 + -12x + x2 = 60

Factor a perfect square on the left side:
(x + -6)(x + -6) = 60

Calculate the square root of the right side: 7.745966692

Break this problem into two subproblems by setting 
(x + -6) equal to 7.745966692 and -7.745966692.

Subproblem 1

x + -6 = 7.745966692 Simplifying x + -6 = 7.745966692 Reorder the terms: -6 + x = 7.745966692 Solving -6 + x = 7.745966692 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 7.745966692 + 6 Combine like terms: -6 + 6 = 0 0 + x = 7.745966692 + 6 x = 7.745966692 + 6 Combine like terms: 7.745966692 + 6 = 13.745966692 x = 13.745966692 Simplifying x = 13.745966692

Subproblem 2

x + -6 = -7.745966692 Simplifying x + -6 = -7.745966692 Reorder the terms: -6 + x = -7.745966692 Solving -6 + x = -7.745966692 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = -7.745966692 + 6 Combine like terms: -6 + 6 = 0 0 + x = -7.745966692 + 6 x = -7.745966692 + 6 Combine like terms: -7.745966692 + 6 = -1.745966692 x = -1.745966692 Simplifying x = -1.745966692

Solution

The solution to the problem is based on the solutions from the subproblems. x = {13.745966692, -1.745966692}

See similar equations:

| -24=5t+35 | | 2(15r+5)+17=7(7r-18) | | 5w+6-w=7w-2(w-3) | | x/22+7=10 | | cos(2x)=sin(4x) | | 24x-x^2=144 | | (x^2+x+6)-(8x-2x)= | | 1/3x^2-1/2x-1/3 | | 1/3x-4/6=7/3 | | -70/-35= | | 3x=7x+1 | | 9(-4)-3y=6(y-6) | | 24+8*2*12= | | 8/(x^2-1)=0 | | -(8n+4)=4n-2(6n+2) | | 5y=7xl | | 5-1m=13 | | -5(1-3x)+3x=-4x+5(5x+2) | | 62+(-5)= | | (31/-4)+(-5/8) | | 4x-4(1+3x)=-(1+5x) | | -5(-8X+2)=26+4X | | 8x+17=22 | | t-3t-7=4t-7 | | 5/6+c=1/3 | | 3(x-5)=7x | | 2x^3+x^2-37x-36=0 | | 5t+12=4-3t | | 3x(x+12)+2x(2x+4)=360 | | x^3+47x-35= | | 2(250-x)+x*4=600 | | -3/b=1 |

Equations solver categories